Zero-Birefringence Silicon Waveguides Based on Tilted Subwavelength Metamaterials - Alaine Herrero-Bermello; Jose Manuel Luque-Gonzalez; Robert Halir; Pavel Cheben; Alejandro Ortega-Monux; Inigo Molina-Fernandez; Aitor V. Velasco (IEEE Photonics Journal)
Polarization independent silicon-on-insulator nanowires are highly sought after, due the inherent high birefringence of this material platform. State-of-the-art designs of non-birefringent waveguides include ridge waveguides and square nanowires, which either imply large dimensions, multiple etching steps, low fabrication tolerances or high wavelength dependence. In this work, we overcome all the aforementioned limitations through tilted subwavelength structures which provide anisotropy control of the resulting metamaterial. With a waveguide cross section of only 300 nm × 550 nm (height × width), the zero-birefringence point is obtained for an approximately $48^°$ -tilt of the subwavelength structure. Birefringence of the nominal design deteriorates by only $9.10^{-3}$ even in the presence of size deviations of $±$ 10 nm. Moreover, birefringence is maintained under $6.10^{-3}$ in a 100-nm bandwidth around the central wavelength of 1550 nm. This innovative approach is readly adaptable to a wide range of waveguide sizes, while maintaining single-etch-step fabrication.